A Review of the Ideal Treatment in the Emergency Department (ED) of Patients with a Suspected Hip Fracture, with a Clinical Audit of one Hospital’s Adherence to Identified Standards. - Taylor, Rebecca (2011)
Background: Hip-fracture is a common orthopaedic injury presenting to the Emergency Department, which is particularly prevalent in the elderly population. The injury is usually very painful and debilitating, the recovery process is long and morbidity and mortality rates following hip fracture is high. To maximise patient outcomes, early surgical fixation of a hip fracture is important, although prior to this, hip-fracture patients also have specific needs within the ED. These include the early administration of effective analgesics and IV fluids, an accurate clinical-assessment of the patient including taking a medical history, and various diagnostic tests including x-rays, blood-tests, a full set of observations and an ECG, in order to confirm hip-fracture, and to exclude any other problems which may need urgent medical attention, or may delay surgery. Aim: To answer the research question ‘What are the standards of excellence for the management of patients with a suspected hip-fracture within the Emergency Department, and does ‘Hospital X’ meet these standards?’ through the process of clinical audit. Method: Following policy and literature review to indentify the evidence–based best-practice standards to care for patients admitted to the ED with a suspected hip-fracture, a retrospective audit of EDIS (Emergency Department Information System) records was carried out, to determine whether ‘Hospital X’ was meeting these standards. Audit Findings: 185 sets of patients’ records were audited. Although it was found that the ED of Hospital X performed well on some standards of the audit, such as the assessment of patients for urgent medical problems, and the medical-assessment and history-taking for patients, J on the whole it was found that the performance of this ED was below the expected standard. Under-achievements were particularly pronounced in the assessments of patient condition by taking full sets of vitals, an ECG and a BM; the assessment and protection of patients from pressure-area damage, including the timely transfer of patients to a bed on a suitable ward; and the timely administration of pain-relief. However, it was noted that the results of this audited may have been affected by the limitations of the method, and the problems accessing the necessary information. Conclusions: Although it was concluded from the ED’s seemingly poor performance in this audit that practice changes may need to be made to improve standards, including the revision of patient pain-assessment and analgesia practices, after reflection and evaluation of the audit process carried out here and its limitations, it is recommended that a re-audit if undertaken to check the quality of the results, and to overcome the problems with accessing data which were experience during this audit. However, the findings of the audit do have some potential implications for future practice and research.